Suppression of leaky expression of adenovirus genes by insertion of microRNA-targeted sequences in the replication-incompetent adenovirus vector genome - Kahori Shimizu; Fuminori Sakurai; Kyoko Tomita; Yasuhito Nagamoto; Shin-ichiro Nakamura; Kazufumi Katayama; Masashi Tachibana; Kenji Kawabata; Hiroyuki Mizuguchi (Molecular Therapy: Methods & Clinical Development, 2014)
Leaky expression of adenovirus (Ad) genes occurs following transduction with a conventional replication-incompetent Ad vector, leading to an induction of cellular immunity against Ad proteins and Ad protein-induced toxicity, especially in the late phase following administration. To suppress the leaky expression of Ad genes, we developed novel Ad vectors by incorporating four tandem copies of sequences with perfect complementarity to miR-122a or miR-142-3p into the 3′-untranslated region (UTR) of the E2A, E4, or pIX gene, which were mainly expressed from the Ad vector genome after transduction. These Ad vectors easily grew to high titers comparable to those of a conventional Ad vector in conventional 293 cells. The leaky expression of these Ad genes in mouse organs was significantly suppressed by 2- to 100-fold, compared with a conventional Ad vector, by insertion of the miRNA-targeted sequences. Notably, the Ad vector carrying the miR-122a–targeted sequences into the 3′-UTR of the E4 gene expressed higher and longer-term transgene expression and more than 20-fold lower levels of all the Ad early and late genes examined in the liver than a conventional Ad vector. miR-122a–mediated suppression of the E4 gene expression in the liver significantly reduced the hepatotoxicity which an Ad vector causes via both adaptive and non-adaptive immune responses.